2020
DOI: 10.1002/nau.24505
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective study for overactive bladder patient treatment satisfaction with mirabegron after being unsatisfied with antimuscarinic therapy (FAVOR study)

Abstract: Aim: We investigated the satisfaction and efficacy of mirabegron in patients with overactive bladder (OAB) symptoms who were unsatisfied with previous antimuscarinic treatment. Methods: This was a 12-week, open-label study of adults with OAB who had been treated with antimuscarinics within 2 years of screening and expressed dissatisfaction over poor efficacy or adverse events of antimuscarinics. All enrolled patients have received mirabegron 50 mg once daily for 12 weeks. The primary outcome was the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 36 A recent multicenter prospective study (the FAVOR study) concluded that mirabegron significantly improved the rates of treatment satisfaction and symptoms in patients with OAB who were unsatisfied with prior antimuscarinic treatment. 37 The response rate of treatment satisfaction at 12 weeks was 69.3% (275/397).…”
Section: Beta-3-agonistsmentioning
confidence: 93%
“… 36 A recent multicenter prospective study (the FAVOR study) concluded that mirabegron significantly improved the rates of treatment satisfaction and symptoms in patients with OAB who were unsatisfied with prior antimuscarinic treatment. 37 The response rate of treatment satisfaction at 12 weeks was 69.3% (275/397).…”
Section: Beta-3-agonistsmentioning
confidence: 93%
“… 26 In the FAVOR study, which included patients after withdrawal of AChs, there were no significant differences observed in mirabegron efficacy between those who discontinued AChs due to low efficacy and those who discontinued due to adverse effects. 27 Generally, the onset of effect in mirabegron recipients is usually observed within 1 month, reaching a maximum within 12–16 weeks after treatment initiation. The effect remains stable over 1 year if the drug is taken regularly.…”
Section: Mirabegronmentioning
confidence: 99%
“…Dear Editor, I read with great interest the article by Ko et al 1 published in a previous issue of the journal. They assessed the satisfaction and efficacy of mirabegron in patients with overactive bladder (OAB) who were unsatisfied with previous antimuscarinic therapy due to poor efficacy and/or adverse events.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Ko et al 1 should be congratulated for a well-designed study on this important topic. However, I would like to contribute to their study with the findings of our recent study investigating clinical responsiveness to antimuscarinics in postmenopausal women.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
See 1 more Smart Citation